2015
DOI: 10.1200/jco.2015.62.8719
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase Ib/II Study of Gemcitabine Plus Placebo or Vismodegib, a Hedgehog Pathway Inhibitor, in Patients With Metastatic Pancreatic Cancer

Abstract: PurposeSonic hedgehog (SHH), an activating ligand of smoothened (SMO), is overexpressed in > 70% of pancreatic cancers (PCs). We investigated the impact of vismodegib, an SHH antagonist, plus gemcitabine (GV) or gemcitabine plus placebo (GP) in a multicenter phase Ib/randomized phase II trial and preclinical PC models.Patients and MethodsPatients with PC not amenable to curative therapy who had received no prior therapy for metastatic disease and had Karnofsky performance score ≥ 80 were enrolled. Patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
337
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 475 publications
(343 citation statements)
references
References 52 publications
4
337
0
2
Order By: Relevance
“…Despite the strong biologic data supporting Hh inhibition in PDAC, two recent studies failed to demonstrate any additional benefit of SMO inhibitors (saridegib and vismodegib) in unselected patients with metastatic PDAC compared with placebo (26,27). Furthermore, in the KPC model of pancreatic cancer, deletion of Shh induced stroma depletion and resulted in an undifferentiated aggressive tumor phenotype suggesting a protective role of Shh and the desmoplastic reaction (28).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the strong biologic data supporting Hh inhibition in PDAC, two recent studies failed to demonstrate any additional benefit of SMO inhibitors (saridegib and vismodegib) in unselected patients with metastatic PDAC compared with placebo (26,27). Furthermore, in the KPC model of pancreatic cancer, deletion of Shh induced stroma depletion and resulted in an undifferentiated aggressive tumor phenotype suggesting a protective role of Shh and the desmoplastic reaction (28).…”
Section: Discussionmentioning
confidence: 99%
“…Interim data analysis indicated that median OS for the saridegib plus gemcitabine arm was less than 6 mo whereas the median OS for the placebo plus gemcitabine arm was greater than 6 mo, resulting in termination of the clinical trial (23). In another randomized, placebo-controlled phase 2 study, the FDA-approved Smo antagonist vismodegib plus gemcitabine was compared with placebo plus gemcitabine in patients with previously untreated metastatic PDA (24). At the time of interim analysis, the OS was 6.3 versus 5.4 mo for vismodegib versus the placebo arm, with an unimpressive hazard ratio of 0.97.…”
Section: Significancementioning
confidence: 99%
“…The authors and other researchers have demonstrated that inhibition of the Hh signaling pathway reduces or suppresses growth of PDA and that SHH primarily acts on the stromal compartment of the tumor [16,17,18,19]. However, despite being demonstrated to have significant anti-tumor functions in pre-clinical animal models, in clinical trials, the Hh inhibitor vismodegib in PDA was not found to improve the response of an unselected cohort [20]. The discrepancy between the expectations that were based on the pre-clinical model and the results of the clinical trial calls for a revision of our theoretical views on the signaling pathways at different stages of tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%